Patriot Games - Phillip Noyce; Archer, Anne.; James Fox; Patrick Bergin; Samuel L Jackson; Sean Bean; Thora Birch; Harrison Ford (USA Paramount Pictures, 1992)
Jack Ryan, the hero of Tom Clancy's techno-thriller series, returns in the sequel to _The Hunt for Red October_. Ryan is on vacation in England when he spoils an assassination attempt on an important member of the Royal Family. Ryan gets drawn back into the CIA when the same splinter faction of the IRA targets him and his family.
When CIA Analyst Jack Ryan interferes with an IRA assassination, a renegade faction targets him and his family for revenge.
Tom Clancy
Language(s): English, Polish, Czech, Hungarian
Subtitle(s): English, Turkish, Icelandic
Keywords: Crime; Drama; Thriller; Action